2015
DOI: 10.3171/2014.10.focus14651
|View full text |Cite
|
Sign up to set email alerts
|

Proposed therapeutic strategy for adult low-grade glioma based on aggressive tumor resection

Abstract: OBJECT There is no standard therapeutic strategy for low-grade glioma (LGG). The authors hypothesized that adjuvant therapy might not be necessary for LGG cases in which total radiological resection was achieved. Accordingly, they established a treatment strategy based on the extent of resection (EOR) and the MIB-1 index: patients with a high EOR and low MIB-1 index were observed without postoperative treatment, whereas those with a low EOR and/or high MIB-1 index re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 25 publications
2
51
0
4
Order By: Relevance
“…For the patients with glioma, the current first line of chemotherapeutics is alkylating agent TMZ and new nitrosourea drugs. Some clinical research has confirmed that the treatment effect of radiotherapy combined with TMZ was better than that of single radiotherapy for patients with glioma who received tumor excision, which can increase the survival rate of patients from 10 to 26% and improve disease prognosis (15). …”
Section: Discussionmentioning
confidence: 99%
“…For the patients with glioma, the current first line of chemotherapeutics is alkylating agent TMZ and new nitrosourea drugs. Some clinical research has confirmed that the treatment effect of radiotherapy combined with TMZ was better than that of single radiotherapy for patients with glioma who received tumor excision, which can increase the survival rate of patients from 10 to 26% and improve disease prognosis (15). …”
Section: Discussionmentioning
confidence: 99%
“…5,9,27,29 Remarkably, further analysis showed that these molecular subgroups could be distinguished based on only a handful of molecular features, including mutation of IDH1 or IDH2 (IDH-mut) and 1p19q-codel, biomarkers independently verified by many studies as hallmarks for distinguishing molecular subgroups in grade II/III glioma. [4][5][6][7]9,13,28,[30][31][32][33][34][35][36][37][38][39] Using these markers alone, most grade II/III tumors can be divided into 3 molecular subtypes: (1) mutation of either IDH1 or IDH2 with 1p19q codeleted (IDH-mut+1p19q-codel), (2) IDH-mut without deletion of 1p or 19q (1p19q intact) or with isolated deletion of 1p or 19q, and (3) no mutation of IDH1 or IDH2 (IDH-wt). 5 Multiple studies have shown that codeletion of 1p and 19q is strongly associated with IDH-mut, such that 1p19q codeletion in IDH-wt tumors is rare.…”
Section: Grade Ii/iii Glioma: Search For Molecular Subgroupsmentioning
confidence: 99%
“…Numerous large studies of patients with brain tumors have shown that among grade II/III gliomas, 1p19q-codel is significantly correlated with improved PFS and OS. 4,6,7,9,10,13,30,32,41,42 Many of these studies used heterogenous populations treated with a variety of approaches, but a few showed statistically significant correlation between 1p19q-codel and outcome within a population of patients who received the same treatment. The independent prognostic value of 1p19q status was also confirmed through multivariate analyses from multiple studies in patients with grade II/III glioma.…”
Section: Grade Ii/iii Glioma: Search For Molecular Subgroupsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 In both LGG subsets, radiotherapy (RT) did not clearly correlate with an OS or PFS advantage. Utilizing results from their retrospective cohort study, these au-thors highlight the predictors of OS and progression-free survival (PFS).…”
Section: Adjuvant Chemotherapymentioning
confidence: 94%